WETLAND DEGRADATION AND LOSS DUE TO THE EXPANSION OF ANTHROPOGENIC ACTIVITIES (International Association of Biologicals and Computational Digest, 2023)
A wetland ecosystem covers about 5-10% of the earth's land. Wetlands play a significant role in the world's economy but they suffer from several threats from various influencing factors. Wetlands are destroyed due to the expansion of human activities and their effect on living and non-living organisms. Some of India’s and Gujarat's wetlands case studies highlight the worst conditions of wetlands from past decades. These case studies highlight the reasons for wetland degradation, and also which types of issues need to be addressed. Wetlands are the most important ecosystem on earth, and to control wetland degradation, it is essential to improve special laws and regulations and be aware of people to conserve ecosystems.
Keywords: Wetlands, Degradation and loss, Ecosystem, Service, Habitat, Urbanization, Economy, destruction